Pengaruh Tari Kreasi Terhadap Pengembangan Motorik Kasar Anak di Taman Kanak-kanak Kemala Bhayangkari 03 Alai - Utari, Annisa Aprilia; Yeni, Indra (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
The study was conducted because based on the facts found in TK Kemala Bhayangkari 03 Alai about the implementation of the development of gross motor children in which children are less able to coordinate their bodies, difficulty in moving forward and backward movements and lack of flexibility of the child's body in making movements. So to find out how much influence the butterfly creation dance in the development of children's gross motor skills at TK Kemala Bhayangkari 03 Alai is the purpose of this research. The method in this study uses quantitative in the form of Quasi Experiment The sampling technique used was purposive sampling, namely class B1 was used as a control and B2 was used as an experimental sample, each consisting of 10 children. The9 results of data analysis obtained from the experimental class 84 with SD 7.68 while the control class was 76 with an SD of 7 obtained through the average test. At the conclusion2that there is the0influence of9dance creations on8the development of9gross motor skills in7kindergarten Kemala Bhayangkari 03 Alai.